2014
DOI: 10.1093/jxb/eru426
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to altitude affects the senescence response to chilling in the perennial plant Arabis alpina

Abstract: SummaryPlants originating from high altitude have an increased capacity for sucrose accumulation in response to chilling and sucrose content is positively correlated with jasmonic acid in accessions from different altitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
6
29
0
Order By: Relevance
“…Compared with the control sample, 925 up-regulated genes and 254 down-regulated genes were identified as DEGs, indicating that the altered genes are involved in regulating the response to cold treatment. Similar to previous reports from many other species, the number of DEGs identified under cold stress was increased compared with the control [2628]. Interestingly, among the 925 up-regulated transcripts, 91 (9.8%) had unknown/unclassified functions (S2 Table).…”
Section: Discussionsupporting
confidence: 86%
“…Compared with the control sample, 925 up-regulated genes and 254 down-regulated genes were identified as DEGs, indicating that the altered genes are involved in regulating the response to cold treatment. Similar to previous reports from many other species, the number of DEGs identified under cold stress was increased compared with the control [2628]. Interestingly, among the 925 up-regulated transcripts, 91 (9.8%) had unknown/unclassified functions (S2 Table).…”
Section: Discussionsupporting
confidence: 86%
“…Hence, the highly induced sucrose transporter genes ( SUC2/7 ) should be important candidates to cope with multiple stress conditions. Previous reports have revealed that both stress and sugar accumulation can promote leaf senescence (Masclaux-Daubresse et al, 2007; Wingler et al, 2015). In the perennial plant Arabis alpina , sugar accumulates strongly in response to cold stress while it is correlated with the senescence dependent decline in chlorophyll at warm temperature (Wingler et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have revealed that both stress and sugar accumulation can promote leaf senescence (Masclaux-Daubresse et al, 2007; Wingler et al, 2015). In the perennial plant Arabis alpina , sugar accumulates strongly in response to cold stress while it is correlated with the senescence dependent decline in chlorophyll at warm temperature (Wingler et al, 2015). The observation that senescence is delayed and not accelerated despite sugar accumulation in the CT and CD can be explained with cold acclimation releasing the sugar-dependent repression of photosynthetic genes (Strand, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…In the European Alps, A. alpina is restricted between 800 and 3000 meters (Huxley 1986). Studies so far have focused on the genetic architecture of flowering and perenniality (Wang et al 2009;Bergonzi et al 2013), leaf senescence (Wingler et al 2012;Wingler et al 2015) and phenotypic traits as root hair and trichomes (Chopra et al 2014). There is an ongoing effort in advancing the molecular knowledge of A. alpina by sequencing its genome (Melodelima and Lobreaux 2013;Lobreaux et al 2014;Willing et al 2015).…”
Section: Introductionmentioning
confidence: 99%